Normal - anders - krank? Akzeptanz, Stigmatisierung und Pathologisierung im Kontext der Medizin - Gross, Dominik; Müller, Sabine; Steinmetzer, Jan (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2008)
The volume brings together a broad spectrum of problem areas, all of which affect the social responsibility of medicine and those involved in medicine. Topics such as transsexuality, homosexuality, body identity disorders, physical and mental disability, compulsory treatment and giftedness are treated - from a historical, scientific-theoretical and ethical point of view. It examines, among other things, the extent to which medicine decides on the acceptance, stigmatization and pathologization of certain minorities and people with different lifestyles, and to what extent it has a role as an "interpretive power". At the same time, it should be worked out that medicine has a special responsibility, especially when dealing with people whose physical or mental disposition is perceived by the general public as "different".